Incidence, factors, and clinical significance of cholesterol crystals in coronary plaque: An optical coherence tomography study. (April 2019) - Fujiyoshi, Kazuhiro; Minami, Yoshiyasu; Ishida, Kohki; Kato, Ayami; Katsura, Aritomo; Muramatsu, Yusuke; Sato, Toshimitsu; Kakizaki, Ryota; Nemoto, Teruyoshi; Hashimoto, Takuya; Sato, Nobuhiro; Meguro, Kentaro; et al.
Abstract: Background and aims: Intraplaque cholesterol crystal (CC) is recognized as a component of vulnerable plaques. However, the clinical characteristics of patients with CC and the impact of CC on clinical events remain unknown. Methods: A total of 340 consecutive patients who underwent optical coherence tomography (OCT) imaging of culprit lesions were included in the study. CC was defined as a thin linear structure with high reflectivity and low signal attenuation on OCT images. The incidence of major adverse cardiovascular events (MACE) at 1-year was compared between patients with CC (CC group) and those without CC (non-CC group). MACE included cardiac death, non-fatal myocardial infarction, target vessel revascularization (TVR), and non-TVR (NTVR). Results: CC was observed in 29% (n = 98) of the patients. There was no significant difference in baseline clinical characteristics between the CC and non-CC groups, other than in eicosapentaenoic acid (EPA)/arachidonic acid (AA) ratio (0.39 ± 0.29 vs. 0.47 ± 0.33, p  = 0.047) and hemoglobin A1c (HbA1c) levels (6.51 ± 0.97 vs. 6.25 ± 0.87%, p  = 0.016). The incidence of MACE and NTVR at 1-year was significantly higher in the CC group than in the non-CC group (15.3 vs. 7.9%, P = 0.038; 8.1 vs. 2.5%, p  = 0.017). The presence of CC was significantly associated with a higher rate of 1-year MACE (odds ratio 4.78, confidential interval 2.02–10.10, p  < 0.001). Conclusions: Patients with CC in the culprit lesion had higher HbA1c and lower EPA/AA than patients without CC. The 1-year clinical outcomes in patients with CC in the culprit lesion were worse than in those without CC. Graphical abstract: Image 1 Highlights: The incidence of cholesterol crystals in culprit lesions requiring PCI was 29%. Lower EPA/AA was associated with the presence of cholesterol crystals. The presence of cholesterol crystals was associated with worse clinical outcomes.